Characterization of 3D printed bolts based on digital image correlation and infrared thermography. (June 2020) - Feng, Xiaowei; Xue, Fei
Abstract: This study selects 3D printing to innovate traditional research approaches regarding bolting. Three bolts composed of different manufacturing materials—aluminum alloy (AL), die steel (DS) and stainless steel (SS)—are successfully 3D printed, and the desired geometric profile is achieved with high precision. Prior to printing, the digital file of the prototype (PT) bolt is obtained by a 3D laser scanning system. Afterwards, mechanical tensile tests, infrared thermography (IRT) tests and digital image correlation (DIC) tests are carried out. The mechanical testing results indicate that the peak strength of the DS bolt is approximately twice that of the PT bolt. The IRT results show that the maximum temperature on the surface of all bolts except the AL bolt increases as the load increases, and the minimum temperature on the bolt surface is barely impacted by loading. DIC indicates a feasible relationship between the load and strain for the PT bolt, AL bolt and DS bolt. Overall, the AL bolt is not suitable for replicating the PT bolt, whereas the DS bolt and SS bolt are suitable choices. The conclusions established in this study provide new measures for future research regarding laboratory bolting tests and even engineering bolting trials. Graphical abstract: Unlabelled Image Highlights: Aluminum alloy, die steel and stainless steel were selected as materials to manufacture bolt via 3D printing technique. Digital image correlation and infrared thermography were selected for displaying deformation (thermal) field. The maximum temperature on bolt surface is sensitive to load change whilst the minimum temperature is stagnant. Die steel and stainless steel are suitable materials for mimic bolt.